Islamic Religious Education and Muslim Youth Identity on Social Media: A Critical Discourse Analysis of Instagram and TikTok Content in Indonesia - Novena Ade Fredyarini Soedjiwo; Fajri Zulia Ramdhani; Suroyo (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2025)
The rapid growth of digital technology has led to the proliferation of social media platforms, significantly influencing various aspects of life, including the formation of religious identity among Muslim adolescents. This study examines the role of Islamic education in shaping Muslim identity in the digital era through critical discourse analysis. Using a qualitative approach, data were collected from social media content related to Islamic education and identity formation. The analysis focuses on how Islamic educational messages are conveyed, received, and interpreted across digital platforms. The findings indicate that Islamic education plays a crucial role in strengthening religious identity among Muslim youth by fostering a sense of belonging and providing moral guidance amid globalization and modernization. The novelty of this study lies in its examination of the intersection between Islamic education and digital media, highlighting social media’s potential as a strategic tool for disseminating Islamic values and countering radical ideologies. This research underscores the importance of leveraging digital platforms to enhance Islamic teaching effectiveness and contribute to the development of a resilient Muslim identity in the contemporary digital landscape, offering insights for educators, policymakers, and religious leaders in promoting positive religious identity and countering extremist narratives. ABSTRAK Munculnya teknologi digital telah menyebabkan proliferasi platform media sosial, yang berdampak signifikan pada berbagai aspek kehidupan, termasuk pembentukan identitas religius di kalangan remaja Muslim. Penelitian ini menyelidiki dampak pendidikan Islam dalam membentuk identitas Muslim di era digital melalui analisis wacana kritis. Dengan menggunakan pendekatan kualitatif, data dikumpulkan dari konten media sosial yang berkaitan dengan pendidikan Islam dan pembentukan identitas. Analisis difokuskan pada bagaimana pesan-pesan pendidikan Islam disampaikan, diterima, dan ditafsirkan di platform media sosial. Temuan penelitian mengungkapkan bahwa pendidikan Islam memainkan peran penting dalam memperkuat identitas religius di kalangan remaja Muslim, memberi mereka rasa keterikatan dan panduan moral di tengah tantangan globalisasi dan modernisasi. Keaslian studi ini terletak pada pemeriksaannya mengenai persimpangan antara pendidikan Islam dan media digital, menekankan potensi media sosial sebagai alat untuk menyebarluaskan nilai-nilai Islam dan melawan ideologi radikal. Penelitian ini menekankan pentingnya memanfaatkan platform digital untuk meningkatkan efektivitas pengajaran Islam, sehingga berkontribusi pada pengembangan identitas Muslim yang tangguh dalam lanskap digital kontemporer. Penelitian ini menawarkan wawasan yang signifikan bagi pendidik, pembuat kebijakan, dan pemimpin agama mengenai penggunaan strategis media sosial dalam mempromosikan identitas religius yang positif dan melawan narasi ekstremis.